By Night, the San Francisco World's Fair Glitters Like a Jewel (H.S. Crocker Co., Inc.)
Seen from Yerba Buena Island by night, the Golden Gate International Exposition on Treasure Island in San Francisco Bay is an inspiring example of the modern art of indirect illumination.